Embryonic stem cells for lung fibrosis Is it the Prometheus myth or the Pandora’s Box? - Tzouvelekis, Argyris; Bouros, Demosthenes (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Three thousand years ago the Greek epic narrativepoet Hesiod introduced to humanity his earliestwork called “Theogony” where he narrates the mythof “Prometheus” who provoked Zeus’ wrath by stealingfire from the Gods and delivering it to humans. ...